Closing the digital divide: Southeast Asia's path towards a knowledge society - Hans-Dieter Evers; Solvay Gerke (University of Bonn, Center for Development Research (ZEF), 2005)
The production, dissemination and utilisation of knowledge are essential for development and the introduction of information and communication technology (ICT) is a precondition for developing a knowledge society. Countries, regions and populations are, however, divided, in terms of access to ICT. Socio-economic indicators on Korea, Malaysia, Singapore, the Netherlands and Germany are used to show that the existing global digital divide and the knowledge gap are widening between developing countries and the industrial countries and within individual nations. Some Southeast Asian countries have embarked on an ambitious plan to close the digital divide and to use knowledge as a base for economic development, by-passing earlier stages of industrialisation. Some commentators have, in contrast, asserted that it is doubtful that closing the digital divide will let developing countries leapfrog to higher levels of development as the knowledge economy will deepen the digital divide between regions and populations and actually expand the gap between rich and poor. The paper discusses this controversy by arguing that global knowledge has to be localized and local knowledge utilized in developing a knowledge society. If it seems unlikely that the digital gap between ASEAN and developed countries will be closed completely at least narrowing the gap at the lower end should be targeted. Statistical data on the global absorption of locally produced knowledge are used to measure the way towards a knowledge society. Singapore, Brunei, Malaysia and the Philippines have relatively high local social science output, whereas Indonesia, Cambodia, Vietnam, Myanmar and Laos have low output rates. We diagnose four different paths from 1970 to 2000: Indonesia shows a stable high level of dependence, Malaysia and the Philippines are increasing local output but also increasing dependence, whereas Singapore is increasing output with decreasing dependence on global social science knowledge.
urn:nbn:de:0202-2008091106
Keywords: 300